Is the statutory standard sale and purchase of house contract in Peninsular Malaysia Islamic? - Md Dahlan, Nuarrual Hilal (2009)
In Peninsular Malaysia, it is well entrenched that the application of the statutory standard sale and purchase agreement (Schedules G, H, I and J) as provided in the Housing Development (Control and Licensing) Regulations 1989, is mandatory for all house purchases pursuant to regulation ll(1) and (1A) of the Housing Development (Control and Licensing) Regulations 1989 and the principles decided in the case law.This paper seeks to examine the provisions contained in the statutory standard sale and purchase agreement (Schedules G, H, I and J) of the Housing Development (Control and Licensing) Regulations 1989 ('the said agreement') of whether the said agreement is compatible with the requirement of Shariah (Islamic Law), insofar as it relates to abandoned housing projects in Peninsular Malaysia.The determination is paramount because due to the execution of the said agreement indicating the equitable or legal ownership of any purported purchase of housing unit and the validity of the purchase, parties to the agreement may later apply for loans to purchase the unit from Islamic banks in Malaysia.As the requirement for Islamic Bank is the upholding of the principles of Islamic Law in its operation, it subtly opens for a question - whether the said agreement too complies with the requirements as set out by Islamic Law? For otherwise, the subsequent loan agreement obtained from Islamic Bank would also contagiously be null and void.